FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI JAGUNG (Zea mays L.) (Studi kasus di Desa Sidodadi, Kec. Patean Kab. Kendal) - Wheny Mentari Iga Harwati; Suprapti Supardi; Dewi Hastuti (Universitas Wahid Hasyim, 2015)
Agriculture became an important sector for rural economy. Corn is important food crops and became superior commodities in Indonesia. Based on Statistics Patean District 2014, Sidodadi is the largest corn producer village of the 14 villages in thisdistrict. This research was done to know the level of corn farmers’ income and to know the factors that influence corn farmers’ income level in Sidodadi Village Patean District Kendal Regency. This research using random sampling method. Population samples taken are as many as 50 farmers that cultivate corn hybrid types. The results from data processing corn farmers’ income level each season (four months) is Rp 6.911.185,00. RC ratio value is 2,38 that mean the feasibility is feasible. The effect of five variables on corn farmers’ income level indicated with R Square = 0,831, which means that income influenced by age, education, experience, land area, and amount of fertilizer are 83,1 percent and 16,9 percent are affected by other variables not included in the model. Simultaneous testing at a significance level (α) = 1% have significant value of 0,000 indicates that age, experience, education, land use, and the amount of fertilizer simultaneously highly significant effect on the level of farmers' income.The results of t-test at a significance level (α) = 5% for the age variable with significant value of 0,035, and experience with significant value 0,018 have partially significant effect on the level of farmers' income.The land area with significant value of 0,000 at significance level (α) = 1% very significant effect on the level of farmers' income partially. Keywords: farmers, corn, income,Kendal.